2017
DOI: 10.3390/geosciences7030067
|View full text |Cite
|
Sign up to set email alerts
|

The Isopach Mapping of Volcanic Deposits of Mount Samalas 1257 AD Based on the Values of Resistivity and Physical Properties

Abstract: A detailed study had been conducted on the sediment of Mount Samalas' volcanic eruption in 1257 AD. Using the framework of the reconstruction of the ancient eruption of Mount Samalas, the first step was to map and analyze the deposits of volcanic sediment. Secondly, we analyzed the effect of geomorphology and the distance function to the isopach thickness. The results show that a combination of methods allowed to provide a high resolution map of the distribution of the thickness of the volcanic deposits, both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 16 publications
1
7
0
1
Order By: Relevance
“…We found several outcrops with different physical characteristics in the southern region of Mount Samalas and Mount Rinjani, so we chose the area as a research location (Figure 1). [5] found that the sediment type of Mount Samalas possesses massive, unconsolidated, unsorted, and multi-model granule size characteristic. Three basic types of classtic sediment of volcanic are: falls, surges, and PDC sediments [6].…”
Section: Materials Geological Study Areamentioning
confidence: 97%
See 1 more Smart Citation
“…We found several outcrops with different physical characteristics in the southern region of Mount Samalas and Mount Rinjani, so we chose the area as a research location (Figure 1). [5] found that the sediment type of Mount Samalas possesses massive, unconsolidated, unsorted, and multi-model granule size characteristic. Three basic types of classtic sediment of volcanic are: falls, surges, and PDC sediments [6].…”
Section: Materials Geological Study Areamentioning
confidence: 97%
“…Volcanic classtic deposits of Mount Samalas can be found in all parts of Lombok Island [5]. The eruption of the eruption of Mount Samalas, particularly in the South and Southwest regions, has composition: Alluvium (Qa), Young volcanic rock (Qhv), Lokopiko (Qvl), and Kalibabak Formation (Tqb) ( Figure 1).…”
Section: Materials Geological Study Areamentioning
confidence: 99%
“…Under the pumice layer there is a layer of breccia sand that covers the clay layer below (Paleo-topography). This layer of quicksand and breccia covers almost the entire island of Lombok (Hiden et al, 2014;Hiden et al, 2017).…”
Section: D Geoelectric Datamentioning
confidence: 99%
“…The third layer is silt and fine sand saturated with water and occurs at an average depth of 39 m from the ground surface. The third layer, which began at a depth of 47 m from the ground surface, is interpreted as the bedrock consisting of sandstone and mudstone [25]. The rock that made up the layers of the bed of the volcanic deposits included clay, gravel, pumice sand, sand, rough pumice granules, silt, and fine black sand [25].…”
Section: Study Sitementioning
confidence: 99%